A REVIEW ON THE ELECTRICITY SUPPLY POLICYON THE PROVINCE OF CENTRAL KALIMANTAN, INDONESIA - Vontas Alfenny Nahan (BALANGA: Jurnal Pendidikan Teknologi dan Kejuruan, 2014)
Recently, blackouts in Palangka Raya, capital city of Central Kalimantan became more and more often. PT. PLN Palangka Raya branch was always put the blame on the dry season that caused the dam in RiamKanan to have dried resulting in the shutdown of their power engine thus to turn off the electricity supply to every area including Palangka Raya. Endowed with rich natural resources including energy resources such as oil and coal, it is unlikely to see that this region was suffered from lack of power. There must be something wrong in the electricity supply policy from central government in the arrangement of energy. This is one of the reasons why this topic is deemed important as the background of the research. This research aims to find electricity supply policy for Central Kalimantan Province by reviewing the current and future electricity supply policy in order to meet the future electricity demand up to 2025. The current electricity consumptions are calculated based on the historical data and future electricity demand for Central Kalimantan. The methodology used in this research is historical analysis to get the trend of the supply and demand and the review of electricity planning of PT. PLN 2006-2025 in order to meet the future electricity demand. The review on the effect of the coal-fired power plant is also discussed to give readers a clear understanding on the effect of coal-fired power plant on human health in long term. Finally, the objective of this research beside to find electricity supply policy for the Central Kalimantan province, is also to give a clear understanding of the consequences our next generation will face by choosing a certain electricity supply policy reflected in the RUPTL made by PT. PLN. Still this research has many limitations which open further research to give more comprehensive electricity supply for Central Kalimantan such as the more accurate data collecting, method used and time constraint.